2019
DOI: 10.1016/j.jtcme.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitex negundo L. seeds in letrozole induced polycystic ovarian syndrome

Abstract: The clinical management of PCOS is multifaceted but often unsatisfactory. The aim of the current study is to evaluate the effect of Vitex negundo L. in the letrozole-induced polycystic ovarian syndrome. Female Sprague-Dawley rats were divided into six groups, each containing 6 animals. Group I (Control) daily received 1% carboxymethylcellulose (CMC) suspension as a vehicle control. Letrozole (1 mg/kg) was administered per orally (p.o) for a period of 21 days for the induction of PCOS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 47 publications
3
46
0
1
Order By: Relevance
“…The mechanisms of these buckwheat effects remain unknown. The stimulatory action of vitex on ovarian cell viability, proliferation, apoptosis, and 17 β -estradiol release is concordant with previous indications on its ability to increase ovarian cell apoptosis [ 41 , 42 ] and steroidogenesis [ 36 , 37 , 38 , 39 , 40 ]. Furthermore, there is the first evidence on the capability of vitex to promote ovarian cell proliferation, resulting in cell turnover and viability.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The mechanisms of these buckwheat effects remain unknown. The stimulatory action of vitex on ovarian cell viability, proliferation, apoptosis, and 17 β -estradiol release is concordant with previous indications on its ability to increase ovarian cell apoptosis [ 41 , 42 ] and steroidogenesis [ 36 , 37 , 38 , 39 , 40 ]. Furthermore, there is the first evidence on the capability of vitex to promote ovarian cell proliferation, resulting in cell turnover and viability.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, there is the first evidence on the capability of vitex to promote ovarian cell proliferation, resulting in cell turnover and viability. These effects explain the stimulatory and therapeutic action of vitex on some ovarian functions reported previously [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Animals were induced to develop PCOS with LTZ at 1 mg/kg b.wt dissolved in 2 mL/kg/day of saline for 21 days [23]. Approximately 0.5 mL of blood samples were collected before and after PCOS induction from the jugular vein.…”
Section: Induction Of Pcos Rat Modelmentioning
confidence: 99%
“…Whereas, Hu et al [74] revealed that the same extract acted as an aphrodisiac [10] having estrogen-like activity and proposed its use in hormone replacement therapy. Kakadia et al [75] studied the potential of Vn seeds to treat polycystic ovarian syndrome.…”
Section: Effect On Reproductive Potentialmentioning
confidence: 99%